Linguopoetic and linguocultural issues in literature - Mokhinur Rakhmiddinovna Sayliyeva (Peerian Journals Publishing, 2022)
The presented article is devoted to the functional-discursive analysis of phraseological units in "Gone with the Wind" by Margaret Mitchell. The article contains an analysis of more than 40 phraseological units and comments on theoretical views on the subject of research.
Keywords: phraseological uni; conceptuality; idiom; equivalence